Meta-Analysis of the Effectiveness of Computer-Assisted Language Learning (CALL) on Students' Arabic Language Ability - Irfan; Hukom, Julham (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2025)
This study aims to comprehensively evaluate the impact of using Computer-Assisted Language Learning (CALL) on students’ Arabic language proficiency through a meta-analytic approach. Eleven studies (k = 11) that met the inclusion criteria were analyzed using a random-effects model to account for variation across studies. The meta-analysis results indicate that CALL has a significant positive effect on students’ Arabic language skills, with an effect size (d) of 1.23 and a significance level of p < 0.01, classified as a large effect. However, the high level of heterogeneity (I² > 75%) suggests substantial variation among the studies. Therefore, future research is recommended to analyze potential moderator variables such as intervention duration, educational level, types of language skills, and types of technology used, in order to better understand the factors that influence the effectiveness of CALL.